Personal names and naming practices in Medieval Scotland - Hammond, Matthew (Studies in Celtic history, 2019)
Personal names can provide a rich and often overlooked window into medieval society, and Scotland's diversity of languages over the course of the Middle Ages makes it an ideal case study. This book offers a range of new methodological approaches to anthroponymy, covering Gaelic, Scandinavian and other Germanic names, as well as names drawn from the Bible, the saints, and secular literature. Individual case studies include a comparison of naming in early medieval Scottish and Irish chronicles; an authoritative taxonomy of Gaelic names drawn from twelfth and thirteenth-century charters; a revolutionary new analysis of the emergence of surnames in Ireland, with implications for Scottish history; a complete linguistic discussion of the masculine Germanic names in the 1296 Ragman Roll; a detailed local case study of saints. names in Argyll which bears on place-names as well; and an examination of the adoption of Hebrew Old Testament names in central medieval Scotland